2017
DOI: 10.1136/bmjopen-2016-014075
|View full text |Cite
|
Sign up to set email alerts
|

Mental well-being of patients from ethnic minority groups during critical care: a qualitative ethnographic study

Abstract: ObjectivesTo investigate the state of the mental well-being of patients from ethnic minority groups and possible related risk factors for the development of mental health problems among these patients during critical medical situations in hospital.DesignQualitative ethnographic design.SettingOneintensive care unit (ICU) of a multiethnic urban hospital in Belgium.Participants84 ICU staff members, 10 patients from ethnic-minority groups and their visiting family members.ResultsPatients had several human basic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…The strategies are predominantly based on the results of an ethnographic fieldwork study in an ICU of a multi-ethnic urban hospital in Belgium (Van Keer et al, 2015;Van Keer et al, 2017) and on additional research on communication during critical care and in multi-ethnic health care settings. These studies were found in the electronic database PubMed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategies are predominantly based on the results of an ethnographic fieldwork study in an ICU of a multi-ethnic urban hospital in Belgium (Van Keer et al, 2015;Van Keer et al, 2017) and on additional research on communication during critical care and in multi-ethnic health care settings. These studies were found in the electronic database PubMed.…”
Section: Methodsmentioning
confidence: 99%
“…This information should also include the hospitals' most important regulations, multicultural health care services and advanced care planning. Information can be provided both within the hospital, for example by nurses and intercultural mediators, and outside the hospital, by general practitioners or migrant organizations (Van Keer et al, 2015;Van Keer et al, 2017).…”
Section: Recruitment Of Nurses With a Different Ethnic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of bilingual nurses also decreases the burden on clients' relatives, ensures that information is more accurately exchanged, and increases trust between staffers and families 37 . There are more possibilities for culturally centered nursing care when providing information to ethnic minority groups both within and outside the hospital regarding multicultural health care services, care planning, and mental well‐being 38 . Nurses should tailor communication skills at the patient or family's level and give them a safe space to think about decisions for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Contacting the participants required anthropological work by the first author FG. Purposive sampling was utilized in order to approach participants during ethnographic fieldwork in suburban areas of Paris and urban areas of Southern Germany, where asylum seekers are commonly located in accommodation facilities (59)(60)(61). This gave the researcher the opportunity to immerse herself into her study field (60).…”
Section: Methodsmentioning
confidence: 99%